Some resulte about the restraction of caristies theorem to continiouse function and the contraction property in banach space - Nsaif, Ansam Ghazi (Journal of College of Education, 2021)
.In this paper ,we show the restriction of Caristi's theorem to contininiouse function can be derived directly from the Zermelo theorem.,on the other hand we consider the completeness and the contraction property in banach space and show that the contraction property implies Lipschitz-completeness or arswise- completeness in a metric spaces .However, in a metric spaces, the contraction property does not imply the usual completeness .